2017
DOI: 10.1590/1519-6984.169442
|View full text |Cite
|
Sign up to set email alerts
|

Changes on physiological parameters of tambaqui (Colossoma macropomum) fed with diets supplemented with Amazonian fruit Camu camu (Myrciaria dubia)

Abstract: The physiological responses of juvenile tambaqui (Colossoma macropomum) fed commercial feed supplemented with different concentrations of camu camu (Myrciaria dubia) were evaluated. The design was completely randomized, with treatments arranged in a factorial design with three proportions of camu camu (15%, 30% and 45%) and a control treatment (100% commercial diet), with four replicates per treatment. A total of 96 tambaqui specimens were used, with a mean initial weight of 11.69 ± 2.68 g and a mean length of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 31 publications
1
26
0
Order By: Relevance
“…Thus, the use of agroindustrial byproducts, such as rice, as demonstrated in this study, can reduce production costs for tambaqui. This has already been demonstrated with the use of cassava (Aride et al, 2016) and camu camu (Myrciaria dubia HBK Mc Vaugh) (Aride et al, 2018).…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…Thus, the use of agroindustrial byproducts, such as rice, as demonstrated in this study, can reduce production costs for tambaqui. This has already been demonstrated with the use of cassava (Aride et al, 2016) and camu camu (Myrciaria dubia HBK Mc Vaugh) (Aride et al, 2018).…”
Section: Introductionmentioning
confidence: 86%
“…to achieve a balanced diet, and provide enough energy to meet their metabolic needs (Mori-Pinedo, 1999). Studies related to tambaqui feeding in their natural environment have been developed in order to identify available products and their energy rates, which makes possible the inclusion of these in diets (Silva et al, 2003;Aride et al, 2016;Aride et al, 2018). Rice has 28% carbohydrate and carbohydrate is essential for metabolic functions such as nourishment of cells and proper functioning of the central nervous system (Institute of Medicine, 2002).…”
Section: Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood parameters have been used to monitor fish health, determine occurrences of stress and aid in analyses on the general state of fish population health (Tavares- Moraes, 2004, 2007;Pavlidis et al, 2007;Aride et al, 2007Aride et al, , 2010Aride et al, , 2018Ferreira et al, 2013;Oliveira et al, 2017a, b).…”
Section: Introductionmentioning
confidence: 99%
“…The high cost of fish feed still is one of the great difficulties, so, it has been sought ever more efficient strategies to minimize these costs, including to know the needs of each nutrient for each species (Portz et al, 2000;Aride et al, 2018;Brasil, 2017).…”
Section: Introductionmentioning
confidence: 99%